ANALYSIS OF INTER-ORGANIZATIONAL KNOWLEDGE SHARING NEEDS AMONG MICRO, SMALL, AND MEDIUM ENTERPRISES WITHIN TRADITIONAL MARKET (Survey on Traditional Market in Malang City) - Rindha Deviana Sari (Fakultas Ilmu Administrasi Universitas Brawijaya, 2013)
Inter-organizational knowledge sharing is the key to improve the performance of Micro, Small, and Medium Enterprises (MSMEs) performance within traditional market. MSMEs within traditional market plays an important role for Indonesian economic activities and its development for a long time. The purpose of this research is to analyze and to investigate the inter-organizational knowledge sharing needs among MSMEs in Indonesia. A questionnaire survey was conducted on MSMEs within traditional market enlisted in the Traditional Market Bureau in Malang City. The survey was conducted in ten selected traditional markets including Besar, Blimbing, Kebalen, Tawangmangu, Bunul, Burung, Sawojajar, Sukun, Bunga, and Wilis. Data were analyzed using generalized structured component analysis (GSCA) that represents a component-based approach. Upon seven variables and out of 99 respondents, the findings show that basically knowledge sharing is critical to be examined among MSMEs within traditional market. The empirical result reveals the urgency of inter-organizational knowledge sharing within traditional market. The better knowledge sharing activities, the better organizational performance can be realized. MSMEs within traditional market need support from many stakeholders such as government, academician, and society. Considering the importance of MSMEs in Indonesia, the finding of this research may be useful for the MSMEs development plan in the future. Keywords: Knowledge sharing, Micro to medium sized enterprises, Traditional market, GSCA